Perencanaan Arsitektur Enterprise Desa Dengan Kerangka Kerja TOGAF ADM - Zanuar Rifai; Trias Bratakusuma; Ratna Arvianti (ISB Atma Luhur, 2020)
The village of Pageraji is one of the village governments located in the western capital of Banyumas Regency. The process of administration services in Pageraji Village still uses conventional systems. Based on the analysis of the problem, researchers will make planning the enterprise architecture to know in detail the business process and the stages in the Pageraji Village hall. The method used is TOGAF ADM by using four stages, namely architecture stage of vision, business architecture, information system architecture, and technology architecture. The overall analysis of the results of 4 phases of TOGAF ADM obtained the conformity between architectural needs and the recommended architecture seen from the results of analysis of requirement management with the four stages of TOGAF ADM. The results of this study are architectural planning companies.